The Influence of Traditional Games on Children's Gross Motor Skills - Rafi Abdul Qahar; Sandi Dwi Triono; Sutiswo (Journal of Physical and Outdoor Education, 2026)
This study has a background problem in the gross motor skills of children at Cipetir 02 Elementary School which are not yet optimal in gross motor skills. This study aims to determine the effect of traditional games on children's gross motor skills. This study uses an experimental method with a pre-test and post-test control group design model conducted on two groups. The population in this study were 74 students in grades 4 and 5 of Cipetir 02 Elementary School. The data collection instrument used the TGMD test. The following are the results of the research data: pre-test results 16.67 and post-test results 20.87. The research hypothesis was tested using the Paired Sample Test with the help of the SPSS program. The results showed a significant effect after being given treatment using various traditional games, indicated by an increase of 18%.